2014
DOI: 10.1017/s0317167100017285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brainstem Involvement in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic neurological disease, which affects young adults at a time when they have to make most of their personal and professional choices. predicting the long-term disability of MS is therefore very important for patients as well as neurologists. it has become even more crucial nowadays with more and more treatment options becoming available.Several prognostic factors of long-term irreversible disability have been described in MS: 1) at onset: ethnicity, sex, age, type of symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…This finding suggests that BAEP is insufficient in neurophysiological evaluation of the brainstem in MS. Knowing that brainstem lesions are good predictors of future disability, the EP score is lacking a good measure of brainstem dysfunction. Our previous two studies have shown that BAEP detects brainstem involvement at a significantly lower percentage than VEMP [21,23]. Therefore, based on this the VEMP score was developed as a potential valid measure of brainstem involvement ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that BAEP is insufficient in neurophysiological evaluation of the brainstem in MS. Knowing that brainstem lesions are good predictors of future disability, the EP score is lacking a good measure of brainstem dysfunction. Our previous two studies have shown that BAEP detects brainstem involvement at a significantly lower percentage than VEMP [21,23]. Therefore, based on this the VEMP score was developed as a potential valid measure of brainstem involvement ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the sensitivity of BR in MS has been confirmed in several previous studies, as well as other neurophysiological methods, MRI has proved to be superior in the confirmation of dissemination in time and space 14,15 . In our study, MRI results showed brainstem lesions in 60% of MS patients and 40% of CIS patients, with no statistical difference between the two groups.…”
Section: Discussionmentioning
confidence: 91%
“…Many factors can cause reduced or absent VEMP responses. Particularly in central pathology, the VEMPs are absent, reduced and/or prolonged which can be an early indicator of pathology (53)(54)(55)(56). Many studies reported reduced or absent VEMPs in patients with cochleovestibular schwannoma (i.e., vestibular schwannoma, see introduction) and reported a strong relationship with tumor size (57).…”
Section: Discussionmentioning
confidence: 99%